Hidden pathway: the role of extracellular matrix in type 2 diabetes mellitus–related sarcopenia - Yiping Sun; Zepeng Zhang; Yufeng Wang; Xingquan Wu; Yahui Sun; Huijuan Lou; Jing Xu; Junjie Yao; Deyu Cong (Frontiers in Endocrinology)
Type 2 diabetes mellitus–related sarcopenia (T2DMRS) is a common complication in elderly and advanced diabetes patients that affects long-term prognosis and quality of life. Skeletal muscle is the main unit of glucose metabolism, and it is surrounded by extracellular matrix (ECM), which is a microenvironment that acts as an efficient highway system. The ECM is essential for cellular communication and nutrient transport and supports muscle cell growth and repair. When this “ECM highway” fails to function effectively because of damage or blockage, the development of T2DMRS can be triggered or exacerbated. In recent years, the ECM has been widely demonstrated to play a critical role in insulin resistance and skeletal muscle regeneration. However, how the remodeling of skeletal muscle ECM components specifically affects the T2DMRS mechanism of action has not been scientifically described in detail. In this review, we comprehensively summarize the T2DMRS-related mechanisms of ECM remodeling, suggesting that collagen and integrins may be potential therapeutic targets.